Tinjauan Yuridis Kepailitan Akibat Pembatalan Homologasi Penundaan Kewajiban Pembayaran Utang - Alifah Zhecarina Kadang; Ipah Farihah; Mustolih Siradj (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
This study aims to evaluate the judge's legal reasoning in the judgment Number: 4/Pdt.Sus. Peace Cancellation/2019/PN.Niaga.Jkt.Pst. Jo. Number 718K/Pdt.Sus-Pailit/2019, as well as how the cancellation of the homologation of the postponement of debt payment obligations led to insolvency. Analysis of the matter between PT Arpeni Pratama Ocean Line Tbk and PT CIMB Niaga in their respective roles as debtor and creditor. Due to the debtor's negligence with the homologated peace document, the creditor petitions the Commercial Court to annul the peace agreement. At the level of the Commercial Court, the court denied the demand for cancellation. The Creditors file an appeal with the Supreme Court in response to the verdict of the Commercial Court Judge. The Supreme Court judge observed in his ruling that he had approved the creditor's motion to reject the reconciliation. This study combines a descriptive-analytical research technique in conjunction with a legal research strategy consisting of a normative juridical or statutory approach and qualitative analysis methodologies. Case research for Decision Number 4/Pdt.Sus.Cancellation of Peace/2019/PN.Niaga.Jkt.Pst. Jo. Number 718K/Pdt.Sus-Pailit/2019 revealed that the judge's legal considerations at the first level were in conflict with several Civil Code articles and the principle of balance in Law Number 37 of 2004 concerning Bankruptcy and Suspension of Temporary Debt Payment Obligations. The judge of the Supreme Court who accepts the petition for peace annulment declares the debtor bankrupt with all legal consequences.